TYPES OF TORCH INFECTIONS AND THEIR TRANSMISSION ROUTES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article discusses the nature of TORCH infections, their risks to the mother and fetus during pregnancy, types of infections, routes of transmission, clinical manifestations, diagnosis, treatment, and prevention. TORCH infections can negatively affect fetal development, causing congenital anomalies, preterm birth, and perinatal mortality. Therefore, early detection and prevention of these infections before and during pregnancy are of great importance. The article also highlights the role of TORCH screening in maintaining women’s reproductive health.
Keywords: TORCH infections, pregnancy, toxoplasmosis, rubella, cytomegalovirus, herpes, placenta, fetus, infectious diseases, prevention, diagnosis, reproductive health.